Efektivitas Dana Desa dalam Menunjang Pembangunan Desa di Pekon Way Ngison Lampung Barat - Devi Yani (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
The research aims to know determine the effectiveness of village funds in supporting village development in Way Ngison Village, Batu Ketulis District, West Lampung Regency. The type of research used in this study is qualitative research by comparing targets and realizations from 2015-2020. From the results of the Village Fund effectiveness test at Way Ngison Village, it shows that the average effectiveness level is 86.44%, including in the quite effective category. By level the highest effectiveness was in 2019 at 99.41% while the lowest level of effectiveness was in 2015 at 64.31%. This indicates that the management of Village Fund Allocation in Pekon Way Ngison has not been implemented optimally. Because the realization of the Village Fund Allocation obtained has not reached the revenue target set in the Village Fund Allocation budget.